Improvements to enforcement of multilateral environmental agreements to control international shipments of chemicals and wastes. Issue 6 (June 2016) - Liu, Ning; Somboon, Vira; Wun'gaeo, Surichai; Middleton, Carl; Tingsabadh, Charit; Limjirakan, Sangchan
Illegal trade in hazardous waste and harmful chemicals has caused severe damage on human health and the environment, and brought big challenges to countries to meet their commitments to related multilateral environmental agreements. Synergy-building, like organising law enforcement operations, is critical to address illegal trade in waste and chemicals, and further improve the effectiveness of environmental enforcement. This article discusses how and why law enforcement operations can help countries to implement chemical and waste-related multilateral environmental agreements in a more efficient and effective way. The research explores key barriers and factors for organising law enforcement operations, and recommends methods to improve law enforcement operations to address illegal trade in hazardous waste and harmful chemicals.